Hegemony and authority in health: The World Health Organization in Indonesian online news coverage on COVID-19 pandemic - Liesna Andriany; Heni Subagiharti; Diah Syafitri Handayani; Annim Hasibuan (Universitas Pendidikan Indonesia, 2023)
The idea of hegemony and authority in language practice do exist in the development of linguistics and critical discourse studies. It attracts great attention at any time, moreover during time of crisis, such as the COVID-19 Pandemic. This study uncovers the realization of the hegemony and authority of the World Health Organization (WHO) in the coverage of the COVID-19 Pandemic by online Indonesian media. More specifically, the focus is on the representation of the hegemony and authority of the WHO and their linguistic realization in Indonesian news discourse. The study used the van Dijk’s framework of Critical Discourse Studies to examine five news reports from five Indonesian media related to the WHO stance and standards in the handling of the COVID-19 Pandemic. The study employed van Dijk’s macrostructure analysis to uncover the surface of the news; and Halliday’s transitivity as the microstructure analysis. Overall, the study found that the online Indonesian media coverage on COVID-19 Pandemic automatedly reinforced and maintained the power and the authority of the WHO. On the one hand, the fact is beneficial for the readers since they will receive coverage with reputable sources. On the other hand, there is a potential that the WHO’s power and authority can be misused to enhanced some parties’ interests, for instance in promoting one’s vaccine brand.